Estimulador galvânico vestibular para fMRI - Manczak, Tiago (2012)
This work presents the development of a galvanic vestibular stimulator to be used in functional magnetic resonance imaging experiments (fMRI). In fMRI experiments it is required the production of somatosensory stimuli in the patient must be sincronized with the fMRI pulse sequence. The stimulator circuits were divided in analog circuits (placed within the magnet room) and digital circuits (placed in the MRI command room). The communication between the circuits is made through optical fiber. fMRI experiments performed with volunteers demonstrated that the proposed stimulator is able to keep the sincronization with the MRI system and can be used to locate the brain areas that are activated by the vestibular system.